English Best practice in aggravating and mitigating factors: Assessment of court decisions on corruption (Komisi Pemberantasan Korupsi, 2022)
Many court decisions on corruption have contained aggravating and mitigating factors that have left the public wondering. This research aims to find out the standard of best practice in aggravating and mitigating factors on corruption cases and measure the fulfillment of those standards in various court decisions. This normative research utilises the statute, case, and conceptual approaches as well as the qualitative analysis method. The research concluded that, (1) circumstances outside the elements of the crime, (2) circumstances that reflect the seriousness or dangerousness of the crime and the defendant, (3) the motive to commit such crime including internal or external reasons (Correspondence Inference Theory), (4) circumstances related to or surrounding the offence, and (5) circumstances related to the personal condition or reputation of the defendant in the community are the standards of best practice in aggravating and mitigating factors; and, that none of the court decisions examined in this research have cumulatively fulfilled those standards.